Strategic management of technology-enabled capabilities : a dynamic capabilities approach to strategically aligned value creation - Pretorius, Marthinus W. (University of Pretoria, 2023)
Thesis (PhD (Technology and Innovation Management))--University of Pretoria, 2021.